Казахстан и Китай: внешние политические приоритеты Казахстана и отношение Китая - K. K. Smagulova; R. A. Matkerimova (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2018)
In article is considered the main directions of foreign policy of Kazakhstan and a role of China in foreign policy of our republic. Тhe article is devoted to the experience of China’s policy in the fields of international economy and collective security within such organizations, as Shanghai Cooperation Organization. Chinese foreign policy concept in current era of globalization is sustainable enough for it to become the world’s second superpower, which directions form the basis of its promotion. Also, we can see the analysis of the methods which are used by Chinese government in such directions like USA, EU, Russia and the evolution of Chinese political, economic and financial relations with major powers of today.